METHODS OF BREEDING AND SEED PRODUCTION IN MONSOON CLIMATE OF THE RUSSIAN FAR EAST - V. I. Leunov; Yu. G. Mikheev (Овощи России, 2017)
Tasks that were posed have been well proven and realized concerning the breeding program for beetroot in monsoon climate of the Russian Far East. The new breeding accessions suitable for further variety development with high immunological, productive and marketable characteristics, increased biochemical parameters, and resistance to highly moist soil and pathogens were developed. The biological and morphological features of growing seed plants in beetroot have been studied using the effective elements of selection with combination of promising agricultural techniques for tilling. Technological methods for early generation and marketable seed production have been improved. The favorable agricultural and climatic areas were found to cultivate seed plants of beetroot and produce the high quality seeds that preserved all biological and horticulturally valuable traits. The varieties of beetroot, such as ‘Uspekh’ (variety type Bordeaux), ‘Primorskaya Cylidricheskaya’ (variety type Granat), ‘Primorskaya 4’ (variety type Bordeaux), breeding accessions ‘POOS 22’ (Bordeaux, Primorskaya) were developed and included in the State Register of Breeding Achievements.